Functional Analysis of NtZIP4B and Zn Status-Dependent Expression Pattern of Tobacco ZIP Genes - Barabasz, Anna; Palusińska, Małgorzata; Papierniak, Anna; Kendziorek, Maria; Kozak, Katarzyna; Williams, Lorraine Elizabeth; Antosiewicz, Danuta Maria (Frontiers in Plant Science, 2019)
Tobacco is frequently considered as a plant useful for phytoremediation of metal-contaminated soil, despite the mechanisms for regulation of uptake and accumulation being largely unknown. Here we cloned and characterized a new tobacco Zn and Cd transporter NtZIP4B from the ZIP family (ZRT-IRT-Like proteins). It complemented the Zn-uptake defective yeast mutant zrt1zrt2, and rendered the wild type DY1457 yeast more sensitive to Cd. Bioinformatic analysis and transient expression of the NtZIP4B-GFP fusion protein in tobacco leaves indicated its localization to the plasma membrane. Real-time q-PCR based analysis showed that it is expressed in all vegetative organs with the highest level in leaves. The Zn status determined transcript abundance; NtZIP4B was upregulated by Zn-deficiency and downregulated by Zn excess. At the tissue level, in roots NtZIP4B is expressed in the vasculature of the middle part of the roots and in surrounding tissues including the root epidermis; in leaves primarily in the vasculature. Bioinformatic analysis identified two copies of ZIP4 in tobacco, NtZIP4A and NtZIP4B with 97.57% homology at the amino acid level, with the same expression pattern for both, indicating a high degree of functional redundancy. Moreover, the present study provides new insights into the coordinated function of NtZIP1, NtZIP2, NtZIP4, NtZIP5, NtZIP8, NtIRT1, and NtIRT1-like in response to low-to-high Zn status. Leaves were the major site of NtZIP4, NtZIP5, and NtZIP8 expression, and roots for NtZIP1, NtZIP2, NtIRT1, and NtIRT1-like. Contrasting expression level in the apical and basal root parts indicates distinct roles in root-specific processes likely contributing to the regulation of Zn root-to-shoot translocation. In summary, new insight into the role of ZIP genes in Zn homeostasis pointing to their overlapping and complementary functions, offers opportunities for strategies to modify Zn and Cd root/shoot partition in tobacco.